What can science and technology studies learn from art and design? Reflections on 'Synthetic Aesthetics'. (April 2017) - Calvert, Jane; Schyfter, Pablo
In this paper we reflect on a project called 'Synthetic Aesthetics', which brought together synthetic biologists with artists and designers in paired exchanges. We – the STS researchers on the project – were quickly struck by the similarities between our objectives and those of the artists and designers. We shared interests in forging new collaborations with synthetic biologists, 'opening up' the science by exploring implicit assumptions, and interrogating dominant research agendas. But there were also differences between us, the most important being that the artists and designers made tangible artefacts, which had an immediacy and an ability to travel, and which seemed to allow different types of discussions from those initiated by our academic texts. The artists and designers also appeared to have the freedom to be more playful, challenging and perhaps subversive in their interactions with synthetic biology. In this paper we reflect on what we learned from working with the artists and designers on the project, and we argue that engaging more closely with art and design can enrich STS work by enabling an emergent form of critique.